2021
DOI: 10.1101/2021.12.27.21268431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron variant: exploring healthcare workers’ awareness and perception of vaccine effectiveness: a national survey during the first week of WHO variant alert

Abstract: Background: As COVID-19 Omicron variant spread in several countries, healthcare workers' (HCWs) perceptions of vaccine effectiveness, booster and worries warrant reassessment. Methods: Online questionnaire among HCWs in Saudi Arabia (KSA) was collected between Dec 1-6, 2021, aiming to assess their Omicron variant's perceptions, worries, and booster-vaccine advocacy. Results: Among the 1285 HCWs participants in the study, two-thirds were females, 41% were nurses,46.4% were physicians, and 50% worked in tert… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
4
4
0
Order By: Relevance
“…In the present study, the most noticeable change in attitude between 2019 and 2022 was that, while pre-pandemic the 46-60 years old group was considerably less vaccine-confident than all other age groups, this was not the case in the post-pandemic cohort. In fact, while none of the differences observed between age groups in the 2022 cohort were statistically significant (which is arguably an important finding in its own right, in agreement with a survey carried out at the onset of the Omicron wave), median VCS appeared to increase with age from 19 in participants under 30 years old to 22 in those over 60 years old [23] . This observation is compatible with previous findings of a survey carried out during the Delta wave, indicating that “younger populations had less willingness to receive vaccinations” [24] .…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the most noticeable change in attitude between 2019 and 2022 was that, while pre-pandemic the 46-60 years old group was considerably less vaccine-confident than all other age groups, this was not the case in the post-pandemic cohort. In fact, while none of the differences observed between age groups in the 2022 cohort were statistically significant (which is arguably an important finding in its own right, in agreement with a survey carried out at the onset of the Omicron wave), median VCS appeared to increase with age from 19 in participants under 30 years old to 22 in those over 60 years old [23] . This observation is compatible with previous findings of a survey carried out during the Delta wave, indicating that “younger populations had less willingness to receive vaccinations” [24] .…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with our study, participants from the study of Muhammad et al reported that face masking (75.7%) and social distancing (96.2%) are the essential precautionary measures to limit the spread of the COVID-19 pandemic [ 32 ]. Similar findings have been reported from Saudi Arabia [ 33 ] that face-masking (77.8%) and social distancing (78.0%) are even more critical than vaccination to prevent COVID-19 spread.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we identified that HCWs in KSA who rely on official local statements from Saudi MOH and CDC were more likely to accept vaccination. Reliance on the latter sources have been previously proven to increase COVID-19 vaccine acceptance in numerous studies from KSA, this study further supports utilizing these sources for accurate and reliable information [15,17,37,38].…”
Section: Discussionsupporting
confidence: 71%